2004
DOI: 10.1097/00004650-200401000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Facilitated Psychotherapy Benefits Students and Children

Abstract: Baccalaureate nursing students who participated in equine-facilitated psychotherapy (EFP) clinical observation found that they could benefit as much from the program as the child clients. By identifying beneficial educational outcomes of this nontraditional learning assignment, the authors hope readers will explore similar possibilities for nurses at various stages of their professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…For instance, attention is increasingly being paid to the use of animal-assisted therapy as a therapeutic technique for individuals who face a broad range of physical and mental health challenges such as cerebral palsy [Bertoti, 1988], seizure disorders [Dalziel, Uthman, McGorray, & Reep, 2003], depression [Souter & Miller, 2007], anxiety [Barker & Dawson, 1998], and trauma recovery [Meinersmann, Bradbery, & Roberts, 2008] in adults, as well as learning disabilities [Cawley, Cawley, & Retter, 1994], emotional disorders [Ewing, MacDonald, Taylor, & Bowers, 2007], and psychiatric diagnoses [e.g., schizophrenia, bipolar disorder; Roberts, Bradberry, & Williams, 2004] in youth. Although there is some research on the effectiveness of such practices, this research is often somewhat limited both conceptually and methodologically [e.g., homogeneous samples, lack of control or comparison groups, unclear or ambiguous treatment foci, and scope of assessment; Bachi, 2012;Kazdin, 2011].…”
Section: Complexity In Instantiations Of Haimentioning
confidence: 99%
“…For instance, attention is increasingly being paid to the use of animal-assisted therapy as a therapeutic technique for individuals who face a broad range of physical and mental health challenges such as cerebral palsy [Bertoti, 1988], seizure disorders [Dalziel, Uthman, McGorray, & Reep, 2003], depression [Souter & Miller, 2007], anxiety [Barker & Dawson, 1998], and trauma recovery [Meinersmann, Bradbery, & Roberts, 2008] in adults, as well as learning disabilities [Cawley, Cawley, & Retter, 1994], emotional disorders [Ewing, MacDonald, Taylor, & Bowers, 2007], and psychiatric diagnoses [e.g., schizophrenia, bipolar disorder; Roberts, Bradberry, & Williams, 2004] in youth. Although there is some research on the effectiveness of such practices, this research is often somewhat limited both conceptually and methodologically [e.g., homogeneous samples, lack of control or comparison groups, unclear or ambiguous treatment foci, and scope of assessment; Bachi, 2012;Kazdin, 2011].…”
Section: Complexity In Instantiations Of Haimentioning
confidence: 99%
“…These range from the more physical concepts such as relaxation training taught on horseback, to more intangible ideas like self-awareness, to abstract schemas of unconscious. Roberts [12], for example, describes the horse as a living, breathing biofeedback machine because it externally reveals internal processes in real time. She discussed how nursing students benefited from EFP while learning how the program worked for their child clients.…”
Section: Theorymentioning
confidence: 99%
“…Stimulated by these anecdotal reports and research into its physical rehabilitative effects, the bulk of the literature on equine activities has examined children and adolescents, with emerging adult literature on equine-facilitated psychotherapy (O' Rourke 2004;Selby 2009). The recent theoretical and empirical literature has suggested the following psychosocial effects for children and adolescents participating in equine-assisted activities (EAA): socialization and companionship, self-esteem enhancement, improvement in personal space/boundary issues and other attachment-related problems, reduction in emotional blunting and incongruence, and improvement in meta-cognition and reflectivity (Karol 2007;Roberts et al 2004;Rothe et al 2005;Schultz et al 2007). Earlier literature suggested that EAA could have psychosocial benefits in the following areas, not specified by population: self-confidence, self-esteem, self-concept, interest in learning/motivation to participate in hippotherapy, improvement in attention span/concentration/listening skills, spatial awareness, and verbal skills (MacKinnon et al 1995a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Physical and occupational therapists, for example, have used therapeutic horseback riding and hippotherapy (terms defined below) to improve posture, balance, and muscle symmetry in children with cerebral palsy (e.g., Engel 1999;MacKinnon et al 1995a, b), while special educators and school psychologists have used therapeutic horseback riding, unmounted activities, and vaulting to address issues of self-efficacy, verbal paucity, attentional shifting, cognitive sequencing, and impulse control in children with comorbid learning disabilities and emotional disturbance/disruptive behaviors (e.g., Roberts et al 2004). Their decision to involve animals has been based either upon observation of the importance of animal companionship to humans in everyday life or on clinical experiences or research suggesting physical health or psychosocial benefits to humans of such involvement.…”
Section: Introductionmentioning
confidence: 99%